2010
DOI: 10.2174/138955710793564098
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Instability (MSI) as Genomic Marker in Endometrial Cancer: Toward Scientific Evidences

Abstract: Endometrial Cancer is the most frequent tumor in western world nations, with 142,000 new cases each year and 42,000 casualties. This form of cancer typically affects women between 55 and 65 years of age, and ranks fourth among female tumors. Endogenous predisposing conditions to endometrial cancer development are: late menopause, early menarche and hyperestrogenism, while hormone replacement therapy, obesity, alcohol, diabetes, and a diet rich in animal fats as well as chronic liver disease, are the exogenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Other histological types tend to have a poorer prognosis, since they are more aggressive (high grade ¼ G3) and present at a more advanced FIGO stage. These include clear cell and serous carcinomas [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other histological types tend to have a poorer prognosis, since they are more aggressive (high grade ¼ G3) and present at a more advanced FIGO stage. These include clear cell and serous carcinomas [2].…”
Section: Introductionmentioning
confidence: 99%
“…Endometrial cancer spreads directly into surrounding tissues, such as corpus uteri and cervix, but disease spread also occurs via lymphatic vessels. Lymphatic drainage of the womb is primarily via the pelvic lymph nodes, which surround the external and common iliac vessels, and then on to the para-aortic lymph nodes [2].…”
Section: Introductionmentioning
confidence: 99%
“…1 Most patients with endometrial cancer present with early disease (International Federation of Gynecology and Obstetrics [FIGO] stage I), where the disease is confined to the uterus. 2 The lymphatic drainage of the uterine corpus is complex, with a bilateral and a bipartite lymphatic pathway. The lower uterine segment drains to the pelvic lymph nodes via the broad ligaments, parametria, and paracervical pathway; the upper segment of the uterine corpus drains into the paraaortic lymph nodes via the infundibulopelvic ligaments.…”
mentioning
confidence: 99%
“…Indeed, MSI can be observed in endometrial cancer, but is never found in normal endometrium, even in LS patients [10]. In cancer cases, there is an association between the absence of expression of either MLH1 or MSH2, the presence of germline mutations in the hMLH1 and hMSH2 genes, and the existence of tumor MSI [13]. In a case report, MSI and loss of expression of a MMR protein were found in endometrial hyperplasia without atypia 7 months before the diagnosis of endometrial cancer, suggesting that DNA repair defect appears early in the carcinogenesis process [14].…”
Section: Discussionmentioning
confidence: 99%